Questões relevantes e aspectos controvertidos em torno do contrato de trabalho intermitente - Spindola, Cibele dos Santos Tadim Neves (2022)
There are few studies with the specific objective of discussing life on board in merchant ships. To help fill this gap, this study used a mixed methods methodology to gain more insight regarding the experience of maritime professionals aboard national flag merchant ships, seeking to understand the effects of their prolonged exposure to the environment and organizational culture of the Merchant Navy. Based on the concepts of analytical psychology, we considered the existence of a specific professional persona, which would mediate the subject's job experiences and which would manifest itself through specific behaviors. Over time, a greater identification with this persona would develop, in a movement that would negatively affect the levels of quality of life at work. To test this hypothesis, this study collected data from 30 male Brazilian nautical officers, at different times of their careers, aboard national flag merchant ships that docked at the ports and terminals of Baía de Todos os Santos, BA. Data collection instruments were: Quality of work life questionnaire – QWLQ-78 (REIS JUNIOR; PILATTI; PEDROSO, 2012); Sociodemographic data questionnaire; Socioeconomic Assessment Instrument (GRACIANO; LEHFELD, 2010); and semi-structured interviews following the script developed by the researcher. The results pointed to the previously hypothesized existence of the persona, whose effects, however, do not seem to affect the levels of Quality of Work Life of seafarers, which was at a satisfactory level or higher for all participants. Seafarers were aware of the difficulties of the profession. They listed as aspects that make them stay in their career the financial return and the perceived advantages of the work versus time-off regime. As negative aspects of the job, social isolation, loss of freedom/confinement and the impossibility of providing face-to-face support to family members were highlighted. We conclude that the persona has a protective aspect for this professional group, allowing them to face the challenges of the job. However, this same persona prevents them from seeing alternatives to face these challenges, keeping them as if they were stuck to the profession. In view of research results, we suggest: greater availability of internet communication devices on board, as well as psychological telecare services to allow seafarers to seek more individualized means to deal with work-on-board related issues; development of work routines more suited to on-board reality, possibly including forums for listening to these professionals and their reality; and development of campaigns that encourage personal and social respect for rest and leisure hours